TYM TEST – novel diagnostic tool to assess cognitive functions – study on inhabitants of social welfare house - Derkacz, Marek; Chmiel-Perzyńska, Iwona; Kowal, Agnieszka; Pawlos, Joanna; Michałojć-Derkacz, Magdalena; Olajossy, Marcin; Marczewski, Krzysztof (Current Problems of Psychiatry, 2011)
Cognitive impairment can affect the daily functioning of older people and worsen their quality of life. The aim of this study was to assess cognitive functions using TYM-test, a new diagnostic tool and to compare obtained test results with the results in MMSE test. The survey was conducted among 65 residents of the Social Welfare Home (SWH) in Lublin. The average age of the study group was 76.2 years ± 12.2. We found the strong correlation between the results obtained in TYM-test and MMSE scale – in the final scoring (p <0.001, R = 0.71), and in the following domains: general orientation: p = 0.001, R = 0.49 and mathematical ability: p <0.001, R = 0.70. The study also shown the correlation between the tests used to assess visual-spatial abilities in both analyzed tests, for TYM sub-test of symbols linking (p = 0.001, R = 0.47), Clock Drawing Test (p = 0.001, R = 0.46) and the relevant subsection of MMSE. Determination of cut-off point at 36 points in TYM-test was associated with the highest sensitivity and specificity for MMSE (p <0.001) and most strongly correlated with the diagnosis of cognitive impairment according to MMSE (p <0.001, R = 0.70). Determination of cut-off point at 30 points in the TYM-test showed a stronger correlation with both – the diagnosis of any cognitive impairment (p = 0.001, R = 0.47) and cognitive impairment associated with dementia (p = 0.001, R = 0.53). It seems that TYM-test is more sensitive indicator of cognitive impairment compared with MMSE scale. Determination of cut-off point at 36 and 30 points may be beneficial for sensitivity in identifying cognitive impairment and cognitive disorders with dementia.